2018
DOI: 10.3390/f9030140
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Correlations for Wood Properties of Hybrid Poplar Clones of Southern Quebec

Abstract: This study aims to understand the phenotypic and genotypic correlations among wood anatomical, physical, and mechanical properties of hybrid poplar clones. Samples were taken from seven clones grown on three sites in Southern Quebec, Canada. Five trees per clone were randomly sampled from each site to measure anatomical (fiber length, fiber proportion, vessel proportion, fiber wall thickness, tension wood), physical (basic density, volumetric, longitudinal, tangential, and radial shrinkage), and mechanical woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
3
5
0
1
Order By: Relevance
“…shrinkage by Koubaa et al (1998b) and Peters et al (2002) but nearly two percentage points higher than Huda et al (2018). The tangential shrinkage found in this study was closer to the values reported for Populus tremuloides than for hybrids (Jessome 1977).…”
Section: Number Of Boardssupporting
confidence: 80%
See 3 more Smart Citations
“…shrinkage by Koubaa et al (1998b) and Peters et al (2002) but nearly two percentage points higher than Huda et al (2018). The tangential shrinkage found in this study was closer to the values reported for Populus tremuloides than for hybrids (Jessome 1977).…”
Section: Number Of Boardssupporting
confidence: 80%
“…The radial and vertical variation in SG are possibly the result of differences in the percentage and size of vessels and fibers in response to crown development as described in P. deltoides by Isebrands (1972); although tension wood and other fiber anatomical properties may also play a part (Bendtsen and Senft 1986;Beaudoin et al 1992;Badia et al 2006;Huda et al 2012). The significant and moderately strong positive correlations we observed between SG and MOR, hardness and screw withdrawal indicate that SG may be a reasonable proxy clonal selection criterion for multiple wood quality traits (Huda et al 2018). SG has previously been shown to be under strong genetic control (Beaudoin et al 1992;Peszlen 1998).…”
Section: Number Of Boardssupporting
confidence: 58%
See 2 more Smart Citations
“…Therefore, although the sampled trees represent a wide range of tree sizes, and the results are indicative of the relationships one could find in such material, care must be taken when generalizing the results to white spruce plantations or natural forest. In addition, phenotypic and genetic correlations may differ [66], so caution is advised when comparing the reported results with those from genetically improved trees.…”
Section: Practical Implicationsmentioning
confidence: 99%